Evolution and Innovation in Toe-to-Hand Transfers - Lin, Yu-Te; Wei, Fu-Chen (Seminars in Plastic Surgery, 2025)
Microsurgical toe-to-hand transfer has revolutionized the reconstruction of missing thumbs and fingers, either from trauma or congenital etiologies, since its introduction in the late 1960s. The subsequent developments by global pioneers have made it a reliable surgical procedure with good functional and aesthetic results, yet acceptable donor site morbidities. This review article aims to highlight some significant concepts, surgical skills, and reconstruction strategies developed at Chang Gung Memorial Hospital over the past four decades, which are pivotal to the current landscape of toe-to-hand transfers practice. Avoiding unnecessary shortening of bone, joint, neurovascular bundle, tendon, and pulley in the amputation stump at the initial emergency management, provision of adequate coverage, and several other factors are essential for good results. Retrograde dissection of the vascular pedicle facilitates a quick and safe toe harvest for less experienced surgeons. Developing a modified great toe and lesser toe wrap-around flap, trimmed great toe, and combined second and third toes allows for optimal thumb and finger reconstruction even for challenging metacarpal hands. Both preservation of the proximal 1 cm of proximal phalanx in the remaining great toe and inclusion of a smaller skin flap from the foot, especially in combined second and third toes transfer for primary wound closure, can ensure minimal donor site morbidities.
Keywords: toe transfers; metacarpal hand; thumb reconstruction; combined second and third toe transfers